Biogeography - Lomolino, Mark V. 1953- (Sinauer Associates, 2006)
This undergraduate text and general reference concentrates on environmental and ecological perspectives to show how they have impacted the evolution, distribution and diversity of species. Updated to reflect current research, the text introduces those with a rudimentary knowledge of biology, geography and earth history to the discipline, then describes the environmental setting and basic biogeographic patterns, earth history and fundamental biogeographic processes, the evolutionary history of lineage and biotas, ecological biogeography, conservation biogeography, and the future of the discipline.